2021
DOI: 10.15388/infedu.2022.06
|View full text |Cite
|
Sign up to set email alerts
|

Educational Robotics Applications for the Development of Computational Thinking in a Brazilian Technical and Vocational High School

Abstract: Nowadays, solving problems is substantial for the social relationship human. Computational Thinking (CT) emerges as an interdisciplinary thought process encompassing mental abilities to help students solve and understand problems. Researchers invest in the methodological proposal of activities aimed at CT stimulation, educational approaches, and the conception of technologies that support these activities' execution. Educational Robotics (ER) is one of these technologies that stand out at different educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…However, we focused on understanding how our educational process quantitatively impacts the CT's skills to validate our proposal presented in [Souza et al 2022]] and, consequently, contribute to the literature with guidelines that can be applied to validate educational processes. In addition, with this study, we could endorse our past studies [Isabelle M. L. et al 2019, Souza et al 2021b, Souza et al 2021a] that indicated ER as an instrument capable of fostering CT skills in TV High School students.…”
Section: Related Workmentioning
confidence: 59%
See 2 more Smart Citations
“…However, we focused on understanding how our educational process quantitatively impacts the CT's skills to validate our proposal presented in [Souza et al 2022]] and, consequently, contribute to the literature with guidelines that can be applied to validate educational processes. In addition, with this study, we could endorse our past studies [Isabelle M. L. et al 2019, Souza et al 2021b, Souza et al 2021a] that indicated ER as an instrument capable of fostering CT skills in TV High School students.…”
Section: Related Workmentioning
confidence: 59%
“…Compared to a traditional curriculum activity in play, ER helps programming, CT development, and sequencing ability [Yang et al 2022]. Besides, in [Souza et al 2021b], we show that contact with computational-based ER can positively impact CT skills; however, this impact could be even more significant if supported by an educational process built to foster CT.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Exploring the intersection of CT and VET revealed three noteworthy papers, each approaching the topic from a distinct angle. These encompassed one empirical research paper, i.e., [75], providing valuable real-world insights, one literature review, i.e., [76], which synthesized existing knowledge, and another that adopted a theoretical approach, i.e., [12], further contributing to the theoretical foundations of this interdisciplinary field.…”
Section: Resultsmentioning
confidence: 99%
“…Their study illustrates how specific tools can cultivate CT skills within crafts and design education. In a different context, Souza et al [75] conducted a study on educational robotics in a Brazilian technical high school, showcasing improvements in student performance as a result of CT integration.…”
Section: Ct-vetmentioning
confidence: 99%